Public and construction workers awareness on concrete dust exposure / Syazwani Nurjayadi - Nurjayadi, Syazwani (Faculty of Architecture, Planning and Surveying, 2013)
The awareness of the effects of the hazardous cement / concrete dusts in Malaysia is lacking in the construction industry itself and also amongst the public. Concrete has been used since the first phase of the starting era in construction and is known as one of the most reliable construction materials. Despite the common usage of concrete, few people are aware of the hazards that it may cause to those who are exposed to it.The objectives of this study would help for a better understanding of this matter as it involves identifying the health effects of cement / concrete dusts exposure and to examine the level of awareness regarding this issue. Safety measures that have be outlined in the Occupational Safety and Health are recommended to be implemented in order to prevent or decrease the exposure.The research involves with the selected construction site of Sierra 16, Southern Puchong and EastPark 82,Bandar Mahkota Cheras whereas these 2 residential developments are recognized as the new prestigious development and are in the progress of completion.From the analysis that have been done, it has been found that the level of awareness and the level of exposure of those who are involved in the construction field itself are much more higher to be compared than others. This is mainly because they are directly exposed to cement / concrete dusts